2014
DOI: 10.1080/10962247.2014.905508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-emulsified fuel on a diesel engine generator’s thermal efficiency and exhaust

Abstract: Water-emulsified diesel has proven itself as a technically sufficient improvement fuel to improve diesel engine fuel combustion emissions and engine performance. However, it has seldom been used in light-duty diesel engines. Therefore, this paper focuses on an investigation into the thermal efficiency and pollution emission analysis of a light-duty diesel engine generator fueled with different water content emulsified diesel fuels (WD, including WD-0, WD-5, WD-10, and WD-15). In this study, nitric oxide, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The presence of water in fuel causes the peak temperature in the combustion chamber lower and contributes to the reduction of thermal NOx during combustion [6,26]. This result similar to studies reported by Badran et al, [27], Syu et al, [28] and Maji et al, [29]. Figure 8 revealed the CO emission under the engine condition of 2200rpm for 5 minutes.…”
Section: Fuel Consumptionsupporting
confidence: 83%
“…The presence of water in fuel causes the peak temperature in the combustion chamber lower and contributes to the reduction of thermal NOx during combustion [6,26]. This result similar to studies reported by Badran et al, [27], Syu et al, [28] and Maji et al, [29]. Figure 8 revealed the CO emission under the engine condition of 2200rpm for 5 minutes.…”
Section: Fuel Consumptionsupporting
confidence: 83%
“…By adding water into diesel, it reduces NO x emissions because of lower combustion temperature which is due to the high latent heat of vaporisation of water, and also increases the brake thermal efficiency due to the increased ignition delay by addition of the lower amount of water to diesel [9]. The addition of water to diesel causes improved atomization and better mixing of air and fuel, as it enhances the combustion and lowers the formation of particulate matter (PM) [10]. It was also observed that by the addition of the higher amount of water to diesel causes a further increment in ignition delay and it lowers the brake thermal efficiency, as water carries no energy that increases the specific fuel consumption per unit power output [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Syu et al (2014) compared the emission performance of water-ethanol microemulsion (WEM) with the performance biodiesel and diesel fuel and noted that the CO emissions from the WEM were higher than that of biodiesel, but lower than those of diesel fuel as a result of larger quench layer created by higher latent heats of evaporation of water and ethanol resulting in cooling effects. Furthermore, according to Ithnin et al (2014), the increased number of OH radicals from water content results in more carbon in the fuel being oxidized to CO.…”
Section: Co Emissionsmentioning
confidence: 99%